MANAGEMENT OF PROCESSES OF IMPLEMENTATION OF STATE INTERACTIVE SERVICES THROUGH INFORMATION TECHNOLOGIES - Dilshoda A. Nuritdinova (QO‘QON UNIVERSITETI XABARNOMASI, 2022)
The article considers the processes of implementation of public interactive services through information technology. Studied the world experience in the provision of information and communication services. The theoretical and methodological foundations and the contribution of foreign and local authors to the consideration of this problem are also considered. It is concluded that public institutions can further help create a healthy business environment by providing the appropriate infrastructure to facilitate the entry of firms into the Internet. Organizations operating in areas with affordable high-speed Internet access will have an advantage over companies that do not have such access. In addition, local organizations will be able to transform the Internet using high-speed inclusiveness to create the latest business opportunities with appropriate consulting and financial support. Providing integrated services, available through a single channel, allows private companies and governments to collaborate.